Improving Knowledge of Pregnant and Postpartum Women Through Community-Based Perinatal Mental Health Education - Ageng Septa Rini; Agus Santi Br. Ginting; Shinta Mona Lisca; Milka Anggreni Karubuy; Salfia Darmi; Vina Wulandari; Rifa Amalia (Universitas Pahlawan Tuanku Tambusai, 2026)
Perinatal mental health is an essential component of maternal health during pregnancy and the postpartum period. Limited knowledge about psychological changes, baby blues, and postpartum depression may affect mothers’ readiness to cope with emotional changes and hinder early detection of mental health problems. Community-based education is a promotive strategy to improve mental health literacy among pregnant and postpartum women. This community service program aimed to improve knowledge of perinatal mental health through community-based education. The program was conducted on July 27, 2026, in Bantarjati Village, Bogor City, involving 15 participants, consisting of 10 pregnant women and 5 postpartum women, with support from Posyandu cadres. Activities included coordination, a pre-test, interactive education using presentations and leaflets, discussion, question-and-answer sessions, and a post-test. Educational topics covered psychological changes during pregnancy and the postpartum period, baby blues, postpartum depression, mental health problems, family support, and adaptive coping strategies. Results: The proportion of participants with good knowledge increased from 20.0% in the pre-test to 86.7% in the post-test, while poor knowledge decreased from 46.7% to 0%. Conclusion: Community-based perinatal mental health education improved knowledge among pregnant and postpartum women and may support psychological readiness and early detection of mental health problems.